Pour une autorité bienveillante : quand le bien-être scolaire fait autorité - Camille Roelens
Various recent reflexions about authority lead to the conclusion that there is a contradiction between the needed « asymmetry » which, for Arendt, is inherent to the authority relationship, and the symmetrisation in rights of the inter-individual relationships. Since it has knowingly been thought and designed as such, the role of the primary school director (/principal ?) in the way it is conceived, experienced and exerted, offers a fascinating overview of the possible answers to this famous paradox : how can an authority that does not exist by law remain in practice ? The goal of this work is to go through this overview, and extract, if possible, some guidelines for the analysis of the contemporary phenomenon of authority. After a brief reminder of the key concepts relatively to the aforementioned contradiction, we will then focus on a possible school director / teachers relationship based on a tolerable asymmetry (part 1). We will study the development of the school director's authority, first relatively to the actors outside the educational team - parents, municipal authority, pupils, institution (part 2), then within the educational team. Thus, we will try to determine the outcome and consequences of the recognition of such an authority by all the concerned actors.